ADVANCING UNDERSTANDING OF SERVICE-LEARNING: A CASE STUDY OF A UNIVERSITY IN MALAYSIA - Fong Wei Diong; Phaik Kin Cheah; Poh Chua Siah (Malaysian journal of learning & instruction, 2025)
Purpose – This study aims to advance the understanding of service-learning within the context of Malaysian higher education, employing multiple qualitative approaches to source information relating to student perspectives whilst critically analysing findings through triangulation. The study explores how service-learning is conceptualized, experienced, and implemented from the viewpoints of university students through focus group interviews, complemented by a systematic examination of institutional documents related to service-learning programmes and policies, and observations of service-learning events. Methodology – The research utilized an exploratory-triangulation design, blending focus group interviews with document analysis and observations to gather comprehensive data. Data was collected through a primary source, involving focus group interviews with 15 students across five groups. The data were triangulated through a document analysis of three course syllabi, 10 faculty websites, 72 news articles, 112 university news publications, three university reports, and the observations from six service-learning events. Data collected from the focus group interviews were analyzed using the thematic analysis method, while those collected using document analysis and observations were used for the purpose of triangulation. Findings – Three themes were constructed relating to the students’ perspectives towards service-learning and they comprised the following: (1) experiential learning activities; (2) academic course; and (3) serving the community. There were a total of 14 sub-themes. It was found that students perceived service-learning as an effective experiential learning tool, combining academic learning with community service, though its adoption is not extensive across the campus, highlighting a need for broader implementation in the curriculum. Significance – It addresses a significant gap in the existing literature by offering insights into the perspectives of students in a non-Western context, particularly the context in Malaysia. In addition, this study provides a nuanced understanding of service-learning in a non-Western context, thus offering valuable insights for educators, policymakers, and practitioners aiming to optimize service-learning practices and align them more closely with student needs and institutional goals. The findings inform a comprehensive strategy for the design and execution of service-learning as an educational approach in higher education.